Multi-species host range of staphylococcal phages isolated from wastewater - Pauline C. Göller (Nature Portfolio, 2021)
The host range of bacteriophages defines their impact on bacterial ecology and diversity. Here, Göller et al. isolate 94 staphylococcal phages from wastewater and determine their host range on 117 staphylococci from 29 species, revealing a predominant multi-species host range and thus great potential for horizontal gene transfer.